(untitled) (Revista Espinhaço, 2023)
Orchid bees (Euglossini) comprise a group of bees with a very important functional role in tropical environments. Males forage for aromatic substances in flowers (preferably orchids) and in turn pollinate them. These bees are more diverse in forested habitats, but they are able to fly long distances, also being found in open environments. In this work, we analyze the assemblage of Euglossini males, during the rainy season, in forest patches that form peatland ecosystems in the upper region of Rio Preto State Park and surroundings, in the Serra do Espinhaço Meridional (SdEM). Samplings with aromatic baits were carried out in a capon forest inside the Park and in another capon forest on the outer edge of the Park between October 2022 and February 2023. A total of 401 males belonging to 11 species and three genera (Euglossa, Eulaema, and Eufriesea). Males of Euglossa leucotricha were the most abundant and occurred throughout the samplings. This species occurs in abundance in elevated areas of SdEM. Males of Eufriesea auriceps and Ef. nigrohirta were also collected in great abundance. These species occur in the hot/rainy season, and, in this study, they showed abundance peaks in different months, indicating a possible decoupling in the competition for resources. Because these bees are polylectic, they are key components in pollination and maintenance of the flora in peatlands.